Clinical Relevance of Plasma Endogenous Tissue-Plasminogen Activator and Aortic Valve Sclerosis: Performance as a Diagnostic Biomarker - Chen, Zhongli; Shen, Ying; Xue, Qiqi; Lin, Bo Wen; He, Xiao Yan; Zhang, Yi Bo; Yang, Ying; Shen, Wei Feng; Liu, Ye Hong; Yang, Ke (Frontiers in Cardiovascular Medicine, 2020)
Background: Aortic valve sclerosis (AVSc), a common precursor to calcific aortic valve disease, may progress into advanced aortic stenosis with hemodynamic instability. However, plasma biomarkers of such a subclinical condition remain lacking. Since impaired fibrinolysis featuring dysregulated tissue plasminogen activator (t-PA) is involved in several cardiovascular diseases, we investigated whether endogenous t-PA was also associated with AVSc. Methods: Plasma t-PA levels were measured in 295 consecutive patients undergoing standard echocardiography and Doppler flow imaging. Multiple logistic regression analyses were used to assess the association between t-PA and AVSc. Receiver operating characteristic curve analysis was performed for determining the diagnostic value of t-PA for AVSc. The performance of adding t-PA to clinical signatures of AVSc was evaluated. Concentration of t-PA was assessed in human sclerotic and non-sclerotic aortic valves by histology and immunohistochemistry analysis. Results: Plasma t-PA was higher in patients with AVSc than in non-AVSc counterparts (median, 2063.10 pg/mL vs 1403.17 pg/mL, p < 0.01). C-statistics of plasma t-PA for discriminating AVSc was 0.698 (95%CI: 0.639-0.758). The performance of t-PA for identifying AVSc was better among male and non-hypertensive patients [C-statistics (95%CI): 0.712 (0.634-0.790) and 0.805 (0.693-0.916), respectively]. Combination of t-PA and clinical factors improved classification of the patients (category-free NRI: 0.452, p<0.001; IDI: 0.020, p=0.012). The concentration of t-PA was three times higher in sclerotic compared to non-sclerotic aortic valves. Conclusion: Elevated circulating t-PA level confers an increased risk for AVSc. Further prospective studies with larger sample size are needed to examine if tPA could serve as a diagnostic clinical marker for AVSc.